ChemInform Abstract: Intramolecular Electrophilic Cyclization of Functional Derivatives of Unsaturated Compounds. Part 3. Reaction of N, 4‐Diarylbut‐3‐enamides with Arenesulfenyl Chlorides. Synthesis of 5‐Aryl‐4‐arylsulfanyl‐2, 3, 4, 5‐tetrahydro‐1H‐1‐benzazepin‐2‐ones. Issue 21 (2nd May 2013) - Vas'kevich, A. I.; Tsyzoryk, N. M.; Staninets, V. I.; Rusanov, E. B.; Vovk, M. V.
Abstract The reaction of N, 4‐diarylbut‐3‐enamides (I), (IV), and (VI) with arenesulfenyl chlorides (II) is studied and the different underlaying mechanisms are discussed.